Faneuil Hall, ca. 1930. - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking northeast from Adams Square towards Dock Square and Faneuil Hall. A variety of motorized vehicles are traveling in the area. Merchants display items in front of storefronts. Pedestrians are crossing the streets and walking the sidewalks. In the foreground are tracks for the electric railway. The Custom House Tower is in the background on the right of the image. Donated by Robert Severy. 6 1/4 x 8 1/16 overall 10 12 1/4 Photographs